The complete mitochondrial genome of leafhopper Koreocerus koreanus (Matsumura, 1915) (Hemiptera: Cicadellidae) - Kai Yu; Hu Li (Mitochondrial DNA. Part B. Resources, 2021)
In this study, the complete mitochondrial genome (mitogenome) of Koreocerus koreanus (Mastsumura, 1915) was sequenced with 16,428 bp in length, which consisted of 37 genes including 22 transfer RNAs genes (tRNAs), 13 protein coding genes (PCGs) and 2 ribosomal RNAs genes (rRNAs). Except COX1 and ATP6 initiated with the TTG, other PCGs started with ATN. The COX1, ND4 and ND4L terminated with an incomplete T, while the remaining PCGs stopped with TAA. Excluding tRNA-Ser1 lacking a DHU arm, 21 tRNA genes with secondary structures were typical of cloverleaf structures. Phylogenetic analysis based on the complete mitochondrial sequences of 28 species (26 Cicadellidae and 2 outgroups) showed that Koreocerus koreanus was clustered into the subfamily Idiocerinae, the complete mitogenome of Koreocerus koreanus provides information for further study of Cicadellidae evolution.